Transcriptome analysis revealed differentially expressed genes in rice functionally associated with brown planthopper defense in near isogenic lines pyramiding BPH14 and BPH15 - Hu, Liang; Yang, Dabing; Wang, Hongbo; Du, Xueshu; Zhang, Yanming; Niu, Liping; Wan, Bingliang; Xia, Mingyuan; Qi, Huaxiong; Mou, Tongmin; You, Aiqing; Li, Jinbo (Frontiers in Plant Science, 2023)
Although rice has many pests, brown planthopper (BPH) in particular is known to cause substantial damage. The pyramiding application of BPH-resistance genes BPH14 and BPH15 has proven effective in enhancing rice defense against BPH.However, the molecular mechanisms underlying BPH14/BPH15-conferred resistance remain unexplained. In this investigation, we analyzed the transcriptomes of near isogenic lines (NILs) containing either BPH14 (B14), BPH15 (B15), or BPH14/BPH15 (B1415), as well as their recurrent parent (RP) 'Wushansimiao'. In total, we detected 14,492 differentially expressed genes (DEGs) across 12 mRNA profiles of resistant NILs and RP at different feeding stages. In the transcriptomic analysis, 531 DEGs appeared to be common among the resistant NILs compared to RP before and after BPH feeding. These common DEGs were enriched in defense response, phosphorylation, and salt stress response. In addition, 258 DEGs shared only in resistant NILs were obtained among the different feeding stages, which were enriched in oxidative stress response, karrikin response, and chloroplast organization.Considering the expression patterns and relevant research reports associated with these DEGs, 21 were chosen as BPH resistance candidates. In rice protoplasts, the candidate DEG OsPOX8.1 was confirmed to increase reactive oxygen species (ROS) accumulation by chemiluminescence measurement. Our results provide valuable information to further explore the defense mechanism of insect-resistant gene pyramiding lines and develop robust strategies for insect control.